2021
DOI: 10.48550/arxiv.2107.07451
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data vs classifiers, who wins?

Abstract: The classification experiments covered by machine learning (ML) are composed by two important parts: the data and the algorithm. As they are a fundamental part of the problem, both must be considered when evaluating a model's performance against a benchmark. The best classifiers need robust benchmarks to be properly evaluated. For this, gold standard benchmarks such as OpenML-CC18 are used. However, data complexity is commonly not considered along with the model during a performance evaluation. Recent studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…We showed that advanced HPO methods are preferable over RS and HB baselines, and that multi-fidelity extensions of popular optimizers improve over their black-box version. Lastly, to reduce computational effort, we would like to study whether we can learn which benchmarks are hard and whether it suffices by executing only a representative subset of the benchmarks [16].…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…We showed that advanced HPO methods are preferable over RS and HB baselines, and that multi-fidelity extensions of popular optimizers improve over their black-box version. Lastly, to reduce computational effort, we would like to study whether we can learn which benchmarks are hard and whether it suffices by executing only a representative subset of the benchmarks [16].…”
Section: Discussion and Future Workmentioning
confidence: 99%